The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1519-99402012000200010
|View full text |Cite
|
Sign up to set email alerts
|

Fezes equina como fonte de inóculo na obtenção de indicadores indigestíveis para estimar a digestibilidade em equinos

Abstract: Foram utilizados quatro cavalos castrados, por meio de delineamento em blocos casualizados. Objetivou-se viabilizar a obtenção in vitro das fibras indigestíveis, FDNi e FDAi, mediante a utilização, como inóculos, de líquido ruminal (LR) e fezes equina (FE), para estimar o coeficiente de digestibilidade nutrientes (CDN) de cavalos. Os tratamentos foram constituídos pelo método direto com a coleta total de fezes (CT) e indireto pelo uso das FDNi e FDAi obtidas por meio dos inóculos, LR e FE. Desta forma, no prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…In an extensive review, Foster et al [36] observed that even if all the variables of the animals used as a source of ruminal inoculum were controlled, the cell wall components of the feed are the main components that could affect the digestibility of dry matter or organic matter in in vitro studies. When equine feces were used as an alternative inoculum source in in vitro trials, significant differences between ruminal inoculum sources were observed for IVDMD and IVNDFD [41]. The objective of the principal component analysis is to reduce the number of variables found in the relative contribution method (Singh method) to a smaller number of orthogonal variables that represent the greatest degree of variation in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In an extensive review, Foster et al [36] observed that even if all the variables of the animals used as a source of ruminal inoculum were controlled, the cell wall components of the feed are the main components that could affect the digestibility of dry matter or organic matter in in vitro studies. When equine feces were used as an alternative inoculum source in in vitro trials, significant differences between ruminal inoculum sources were observed for IVDMD and IVNDFD [41]. The objective of the principal component analysis is to reduce the number of variables found in the relative contribution method (Singh method) to a smaller number of orthogonal variables that represent the greatest degree of variation in the study.…”
Section: Discussionmentioning
confidence: 99%